Shanghai’s Old Town: the Challenges of Urban Renewal and Strategies for the Protection of Built Heritage - Knyazeva, Katya (International Planning History Society Proceedings, 2022)
Shanghai’s old town (laochengxiang) has every quality of a living historic district in the centre of a modern metropolis. Its archaic, small-grain and varied urban form is inhabited by a long-standing local community with strong familial connections to the city. But in the absence of effective conservation mechanisms, the old town’s built environment and social fabric are in danger of disappearance, as large pieces of its territory are handed over to commercial developers. The fast pace of blanket modernisation exposes a glaring need for better frameworks of heritage protection. Focusing on the on-going urban renewal project of the Qiaojia Road area, this article illuminates the challenges of heritage management under the pressure of urban development and discusses strategies and attitudes necessary to safeguard Shanghai’s historic urban landscape.